(untitled) (INNOVATIVE ECONOMY, 2025)
Kozhan S.V. ANALYTICAL SUPPORT FOR FORECASTING INSURANCE MARKET DEVELOPMENT BASED ON THE EVALUATION OF INSURANCE PORTFOLIOS AND CLUSTERING OF INSURERS Purpose. The aim of the article is to substantiate an approach for the analytical support of forecasting the development of the Ukrainian insurance market based on the assessment of the quality of insurance portfolios and the clustering of insurers, combining a theoretical generalization of market structuring approaches with practical recommendations for forecasting and risk management. Methodology of research. The work uses a set of scientific methods: generalization of theoretical approaches (integration of domestic and foreign experience in analytical support for the development of the insurance market), statistical analysis (assessment of the scale of activity, risks and profitability of insurers), comparison of performance indicators (identification of market leaders and adequacy of tariff policy), correlation analysis (study of the relationship between the level of payments and profit margins of insurers), hierarchical clustering method (AHC) (allocation of homogeneous groups of non-life insurers and insurers of compulsory motor third party liability insurance according to insurance premiums, level of payments and profit margins). Findings. A clear structure of the non-life insurers market and the segment of compulsory motor vehicle liability insurance were identified, and clusters of companies with different levels of risk and financial stability were highlighted. It was shown that companies’ financial results depend more on the efficiency of expense management and investment activities than on pure loss ratios. The combination of statistical analysis and clustering enables forecasting companies’ stability and determining effective tariff policies. Originality. A comprehensive approach to analytical support for insurance market forecasting was developed, integrating the theoretical generalization of insurer performance assessment methods with practical tools for clustering and risk analysis. It was demonstrated that combining classical statistical methods with market structuring improves the accuracy of forecasting models and allows accounting for the internal heterogeneity of insurers. Practical value. The proposed approach provides a basis for managerial decision-making: portfolio optimization, tariff and underwriting adjustments, forecasting financial stability, enhancing the efficiency of risk-oriented regulatory oversight, and market segmentation for investors. The results allow for combining an analytical framework with practical application under the real conditions of the Ukrainian insurance market. Key words: insurance market, cluster analysis, financial stability, insurance portfolios, tariff policy, forecasting, compulsory motor third party liability insurance, risk, market structuring.